Teacher Identity, Islamic Behavior, and Project-Based Learning Methods for Madrasah Teachers: A Phenomenological Approach - Syahraini Tambak; Desi Sukenti; Ilyas Husti; Zamsiswaya Zamsiswaya; Choirul Mahfud (Universitas Muhammadiyah Yogyakarta, 2023)
Developing students' scientific thinking in aqeedah and akhlaq (moral theology) is urgent, and a project-based learning method is needed for that process. This study explores how teachers can experience their Islamic behavior with their identities and impact project-based learning methods in learning moral theology in madrasah aliyah (Islamic high schools). This study uses a phenomenological approach to explore the Islamic behavior and identity of teachers in madrasah aliyah in developing project-based learning methods. A total of 20 moral theology teachers are involved in this study, and in-depth interviews are conducted to uncover the narratives of teachers' practices in utilizing project-based learning methods. The thematic analysis of two-group interviews with 20 teachers showed that Islamic behavior teachers' personal beliefs provided a religiously motivated narrative framework that facilitated interpreting one's experiences. Islamic behavior and teacher identity play a role in developing project-based learning methods based on moral theology. Islamic behavior is the main bond in developing project-based learning methods and the attribution of identity from God-given personality to learning in moral theology. Teacher identity, Islamic behavior, and students' scientific thinking develop when learning moral theology. Islamic behavior and the personal identity of madrasah teachers can improve project-based learning methods